PENGGUNAAN MEDIA PEMBELAJARAN UNTUK MENINGKATKAN PEMAHAMAN MATEMATIKA SISWA PADA PEMBELAJARAN THEOREMA PYHTAGORAS - Putra, Imam Setiadi; Islamiati, Nur; Komalasari, Lala Intan (IKIP Siliwangi, 2020)
This Study focuses on the use of mathematics learning media in increasing students' mathematical understanding in the learning of the Pythagorean theorem. The research subjects were taken as many as 15 students of class VII in one school in the district of Donggo. The research subjects were randomly drawn to participate in learning using manipulative media. There are two learning media designed for research, namely ICT and Non-ICT media. The results of this study indicate that the use of instructional media can improve students 'mathematical understanding, this is indicated by an increase in the average value of students' mathematical understanding before the use of media 36,93 and after using the media of 80,33. In addition, the results of this study also indicate that there is an influence of the use of instructional media to increase student understanding of learning theoremagas theorem, this is based on the results of the calculation of t-sample test related to Paired-Sample Analysis of two-tailed T-test T-test obtained by ttcount = -12,88 and ttable = 1.753 for a significant level of 5% with df = 14, where 12,88 ≥ -1.753.